Variability of chloroplast DNA and nuclear ribosomal DNA in cassava (Manihot esculenta Crantz) and its wild relatives - Fregene, Martin A.; Vargas, J.; Ikea, J.; Angel, F.; Thome, J.; Asiedu, Robert; Akoroda, M.O.; Roca, W. (1994)
Chloroplast DNA (cp) and nuclear ribosomal DNA (rDNA) variation was investigated in 45 accessions of cultivated and wild Manihot species. Ten independent mutations, 8 point mutations and 2 length mutations were identified, using eight restriction enzymes and 12 heterologous cpDNA probes from mungbean. Restriction fragment length polymorphism analysis defined nine distinct chloroplast types, three of which were found among the cultivated accessions and six among the wild species. Cladistic analysis of the cpDNA data using parsimony yielded a hypothetical phylogeny of lineages among the cpDNAs of cassava and its wild relatives that is congruent with morphological evolutionary differentiation in the genus. The results of our survey of cpDNA, together with rDNA restriction site change at the intergenic spacer region and rDNA repeat unit length variation (using rDNA cloned fragments from taro as probe), suggest that cassava might have arisen from the domestication of wild tuberous accessions of some Manihot species, followed by intensive selection. M. esculenta subspp flabellifolia is probably a wild progenitor. Introgressive hybridization with wild forms and pressures to adapt to the widely varying climates and topography in which cassava is found might have enhanced the crop's present day variability.